Drag Reduction Properties of Nanofluids in Microchannels - Abdulbari, Hayder A.; Fiona Ling, Wang Ming (Sultan Qaboos University, 2015)
An experimental investigation of the drag reduction (DR) individualities in different sized micro channels was carried out with nanopowder additives (NAs) (bismuth(III) oxide, iron(II/III) oxide, silica, and titanium(IV) oxide) water suspensions/fluids. The primary objective was to evaluate the effects of various concentrations of NAs with different microchannel sizes (50, 100, and 200 μm) on the pressure drop of a system in a single phase. A critical concentration was observed with all the NAs, above which increasing the concentration was not effective. Based on the experimental results, the optimum DR percentages were calculated. The optimum percentages were found to be as follows: bismuth III oxides: ~65% DR, 200 ppm and a microchannel size of 100 μm; iron II/III oxides: ~57% DR, 300 ppm, and a microchannel size of 50 μm; titanium IV oxides: ~57% DR, 200 ppm, and a microchannel size of 50 μm, and silica: 55% DR, 200 ppm, and a microchannel size of 50 μm.